Reset observer-based fault tolerant control for a class of fuzzy nonlinear time-delay systems. (January 2020) - Pourdehi, Shabnam; Karimaghaee, Paknosh
Highlights: The problem of actuator fault estimation and fault tolerant observer-based control for a class of nonlinear time-delay systems using Takagi–Sugeno (T-S) fuzzy models is investigated. The introduction of the reset element in the observer can decrease the overshooting and settling time of the estimation process. The observer to be designed is assumed to have norm- bounded gain perturbations. Based on Lyapunov–Krasovskii approach, the existence of adaptive reset observer and the fault tolerant controller with guaranteed asymptotical stability are synthesized. The proposed fuzzy reset observer is applied to Chua's chaotic system and two-stage chemical reactor with delayed recycle streams and the effectiveness of the proposed method is tested by simulation. Abstract: The problem of actuator fault estimation and observer-based fault tolerant control for a class of nonlinear time-delay systems using Takagi-Sugeno (T-S) fuzzy models is investigated. The introduction of the reset element in the observer can decrease the overshooting and settling time of the estimation process. The observer to be designed is assumed to have norm-bounded gain perturbations. Based on Lyapunov–Krasovskii approach, the existence of adaptive reset observer and the fault tolerant controller with guaranteed asymptotical stability are synthesized. All the obtained results are given in the form of linear matrix inequalities (LMIs). Finally, the proposed fuzzy reset observer is applied to Chua's chaotic system and a two-stage chemical reactor with delayed recycle streams. So, the effectiveness of the proposed method is tested by simulation.